Effectiveness of Distraction Techniques Watching Movies on Menstrual Pain Levels of Adolescent Girls - Fitri, Dwi Elka; Lexi, Sri Agnes; Anggreini, Silvia Nora; Ayudytha, Awaliyah Ulfah; Utari, Mona Dewi (Indonesian Journal of Global Health Research, 2024)
Dysmenorrhea is not merely a common gynecological issue but a significant health concern that can lead to psychological distress, impaired daily functioning, and increased health risks. Prevalence dysmenorhea in Pekanbaru, with rates reaching as high as 94.4% among adolescent girls. Distraction techniques involving movie-watching have demonstrated significant potential in reducing pain. The purpose of this study was to determine the effectiveness of distraction techniques watching movies on the level of menstrual pain in adolescents girl. This research is a quantitative study using a quasi-experimental approach with a one group pre and post test research design. The sample in this study amounted to 30 respondent with purposive sampling technique. The implementation. The implementation of this study was carried out by giving a pre-test first, then proceeding with the intervention of watching a movie for 120 minutes, then giving a post-test. from the results of the Paired sample T test analysis test, the P value = 0.000, where the Pvalue is smaller than the Apha value (0.05). It can be concluded that distraction techniques watching movies is effective in reducing menstrual pain in adolescent girl at Public High School 14 Pekanbaru.